APLIKASI KURSUS KOMPUTER ONLINE MENGGUNAKAN PHP PADA LEMBAGA KURSUS KOMPUTER YOGZ COURSE - Kusniyati, Harni; Mursidigama, Yoga Hapsara (PETIR, 2019)
Computer course institute Yogz Course is a computer education institution that provide computer training services. But then, for the time being, the numbers of participant slowly reduced. The reason of this issue is because most of the participants constrainted by travalled distance to the course location and not rarely somehow course schedule clashed with other activities. Because of that for settling this issue, it is necessary to build an online course application that can be accessed anytime and any where without constrainted by time and distances as long as connected to the internet. This research goes in a certain direction for producing a simple web based online computer course application, small, and solid in filling all of the requirement of Yogz Course institution by creating a method of flexible learning and teaching process but still in line with it curriculum and scoring standard, and also without overrided user friendly element to the end users. To build this application, the method applied is System Development Life Cycle (SDLC), consist of Communication (Analysis Requirement), Planning, Modeling, Construction, Deployment. This application coded with programming languages such as PHP, HTML and CSS, plus MySQL as database. The result of this research is website of Yogz Course online computer course. With this online course application, it is expected can give an easy way for course institution in recruiting more participants and facilitate the participants for going through in learning and teaching process without any worry of constrainted by the time and distance as long as internet media available, but still in line with the curriculum applied by the institution.